ORGANIZATIONAL BEHAVIOR CONCEPTS, INSIGHT & MANAGERIAL IMPLICATIONS - Shazaitul Azreen Rodzalan; Eta Wahab; Nor Hazana Abdullah (Penerbit UTHM, 2025)
This book provides a comprehensive yet accessible introduction to Organizational Behavior, focusing on how individual attitudes, emotions, and behaviors shape effectiveness within organizations. By integrating foundational theories with real-world workplace examples, it offers readers a clear understanding of how people interact at individual, team, and organizational levels. Covering key topics such as personality, perception, motivation, leadership, teamwork, organizational culture, and change, the book emphasizes practical application alongside ethical and professional awareness. Designed for students and aspiring professionals, it equips readers with the knowledge and insights needed to navigate contemporary organizational challenges, adapt to change, and contribute positively and confidently to today’s dynamic work environment.